(untitled) (Agroindustria, Sociedad y Ambiente, 2019)
Yogurt is a food with attractive qualities for the incorporation of probiotic microorganisms and thus increase the nutritional properties, however, food products must be subject to a sensory evaluation to adapt to the tastes of the consumer and achieve acceptance and positioning in the market. In this sense, it was proposed to sensorially evaluate a probiotic yogurt applying intensity scale and CATA questioning methodologies, based on consumers. The yogurt was made with two wild strains of Lactobacillus plantarum and two proportions of strawberry jam and gelatin, obtaining 8 different formulations. Fifty potential consumers were used in each test, measuring in both cases the acceptability of the yogurt with a structured hedonic scale of 9 points. To describe the ideal product and yogurt, 9 sensory attributes were used in the intensity scale test and 20 sensory descriptors in the CATA questions methodology. The acceptability of the evaluated product was 4.9 to 7.7 with intensity scale and 4.7 to 6.8 with the CATA questions methodology, where the highest values were assigned to the formulations with the highest content of strawberry jam. The ideal yogurt was described with yogurt flavor, strawberry flavor, strawberry aroma, consistent, acid and sweet. It is concluded that it is possible to make yogurts with Lactobacillus plantarum strains pleasant to the consumer using a proportion of 30% of strawberry jam and 0.8% of gelatin.